Arquivos censurados de Nelson Rodrigues: uma leitura crítica nas redes da criação - Lima, Erickaline Bezerra de (2016)
Nelson Rodrigues (1912-1980) author who introduced the scenic modernity in Brazil, also became known for portraying in his works, an obscure world taken by obsessive and disturbed characters, such characteristics were decisive for the censorship of Rio de Janeiro and Sao Paulo accompany him throughout his artistic career. In this thesis, we bring to light cases of censorship São Paulo, of the 40 to 60, referring to the three theatrical works: Lady of the Drowned, Forgive me for me and betray Golden Mouth; which were provided by Miroel Silveira Archive - AMS School of Communication and Arts ECA-University of São Paulo USP. Through the process called Critical approach (SALLES, 2008a), as an extension of Genetic Critic, problematize some factors that have gone through the creative process of theatrical works of the playwright. For this explanation, we were guided by the concept of Creation Network, which was proposed the construction of a Rodriguean creation, which in our reading includes: the philosophical term deformation (DIDI-HUBERMAN, 2010); self-criticism; and censorship. We propose a reading of 17 theatrical playwright parts and, in particular files on censorship, because they indicate a specific time of the construction work to contain documents that were kept out of reach of the author. In comparison process documents versus work published several modifications were mapped. Built, so this complex network bounded by our critical reading, however, able to bring us closer to the playwright that marked an era and continues the contemporary to unsettle us with their unpleasant Theatre.